The Influence of Viral Marketing, Brand Image, Perceived Value, and Pricing Strategy on Impulsive Buying of the Glad2Glow Brand on Gen Z in East Java - Annisa Oktalia Damayanti (Universitas Negeri Surabaya, 2026)
The beauty industry in Indonesia is currently experiencing rapid growth, particularly in skincare products. This has led to the emergence of many local skincare products, each with its own unique characteristics and strategies, including Glad2Glow. This study aims to analyze the influence of Viral Marketing, Brand Image, Perceived Value, Pricing Strategy on Impulsive Buying on local skincare products Glad2Glow, especially among Generation Z in East Java. Glad2Glow is one of the local skincare brands that has succeeded in attracting the attention of Gen Z through a digital promotional strategy based on Viral Marketing with competitive prices. This study uses a quantitative method to 200 Gen Z respondents in East Java who have purchased Glad2Glow products online at Shopee, Tiktok and Lazada Multiple linear regression analysis techniques. The results show that Viral Marketing (X1) and Brand Image (X2) have no significant effect on Impulsive Buying. While Perceived Value (X3) and Pricing Strategy (X4) have a significant effect on Impulsive Buying. These findings emphasize the importance of the right promotional strategy and consumer perception value in forming spontaneous purchasing decisions, especially among Gen Z who are very active on social media and exposed to digital beauty trends. This study is expected to provide theoretical contributions in the field of marketing as well as become a practical reference for local skincare business actors. Keywords: Brand Image, Impulsive Buying, Perceived Value, Pricing Strategy, Viral Marketing.